Anthropometric indices of obesity and hypertension in different age and gender groups of Croatian population - Ivičević Uhernik, Ana (Array, 2009)
Summary: The aim of this study was to investigate the association of hypertension with the obesity indices – body mass index and waist circumference. The study was based on the data from the Croatian Adult Health Survey 2003, which is a cross-sectional study on the representative sample of 9,070 Croatian adults. The results showed that in both men and women aged 18–64 years and 65 years and older increased BMI and waist circumference were associated with higher odds of hypertension. Odds of hypertension for obese (BMI ł 30) and persons with abdominal obesity (waist circumference ł 102 cm for men, ł 88cm for women) was higher among young and middle aged than among elderly persons. No differences in odds of hypertension were recorded between persons with increased BMI and persons with increased waist circumference. Both BMI and waist circumference exhibited equally strong association with hypertension in Croatian population, in both men and women, and in those who are below or over 65 years of age